The Relationship between Intra-Amniotic Sludge and the Amniotic Fluid Proteome in a Cohort of Pregnant Women with Acute Cervical Insufficiency: A Pilot Study - Rachelle N. M. Govia; Kenzie D. Birse; Adam D. Burgener; Vanessa Poliquin; Savas M. Menticoglou; Christy L. Pylypjuk (Clinical and Experimental Obstetrics & Gynecology)
Background: We aim to determine the relationship between intra-amniotic sludge and the amniotic fluid proteome in cases of acute cervical insufficiency. Methods: This was a secondary analysis of data from an existing prospective cohort of women with acute cervical insufficiency. Amniotic fluid had previously been analyzed by Gram stain, culture and proteomics perioperatively. Post-processing review of stored ultrasound images to evaluate for the presence of intra-amniotic sludge (IAS) was performed by two blinded and independent observers. Results, lab, clinical, proteomic and outcome data were compared between groups with and without sludge. Results: Ten participants with acute cervical insufficiency from the initial cohort were included [IAS group (n = 4) and non-IAS group (n = 6)]. 75% of participants with sludge had negative Gram stain and culture compared to 17% amongst cases without sludge. 18 proteins (3.3%) were differentially abundant between the 2 groups (p < 0.07): the non-IAS group demonstrated increased immune, stress and inflammatory signatures with decreased signatures of keratinization relative to the IAS group (p < 0.05). Conclusions: These preliminary findings suggest that proteomic profiles of amniotic fluid with and without sludge tend to differ. Sludge is associated with an abundance of keratinizing proteins while inflammatory proteins predominate in the absence of sludge. The exploratory nature of this study illustrates the need for future large-scale prospective studies to determine the utility of intra-amniotic sludge and proteomics as markers of intra-amniotic infection in the management of acute cervical insufficiency.